1994
DOI: 10.1128/aem.60.4.1213-1220.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and DNA sequencing of bgaA, a gene encoding an endo-beta-1,3-1,4-glucanase, from an alkalophilic Bacillus strain (N137)

Abstract: The gene bgaA encoding an alkaline endo-beta-1,3-1,4-glucanase (lichenase) from an alkalophilic Bacillus sp. strain N137, isolated in our laboratory, was cloned and expressed from its own promoter in Escherichia coli. The nucleotide sequence of a 1,416-bp DNA fragment containing bgaA was determined and revealed an open reading frame of 828 nucleotides. The deduced protein sequence consists of 276 amino acids and has a 31-amino-acid putative signal peptide which is functional in E. coli, in which the BgaA prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Identical amino acids are shaded in black and similar amino acids in grey. The box indicates the proposed catalytic domain of prokaryotic endo-β-1,3-1,4-glucanases (Tabernero et al, 1994) fuzzy band pattern disappeared and turned into discrete bands after the endo H treatment, the apparent molecular weights of the proteins were still larger than 90 kDa. In general, cell wall proteins with C-terminal Ser-and Thr-rich regions are heavily O-glycosylated (Klis et al, 2002).…”
Section: De(i/l)dxementioning
confidence: 99%
See 1 more Smart Citation
“…Identical amino acids are shaded in black and similar amino acids in grey. The box indicates the proposed catalytic domain of prokaryotic endo-β-1,3-1,4-glucanases (Tabernero et al, 1994) fuzzy band pattern disappeared and turned into discrete bands after the endo H treatment, the apparent molecular weights of the proteins were still larger than 90 kDa. In general, cell wall proteins with C-terminal Ser-and Thr-rich regions are heavily O-glycosylated (Klis et al, 2002).…”
Section: De(i/l)dxementioning
confidence: 99%
“…In addition to the amino acid sequence similarity of YlCrh1p and Ylcrh2p to S. cerevisiae Crh1 and Crh2 proteins, YlCrh1p and YlCrh2p have a DE(I/L)DXE motif that is the hypothetical catalytic domain of S. cerevisiae Crh1p WT Ylcrh1 Ylcrh1Ylcrh2 Ylcrh2 10 5 10 4 10 3 10 2 10 1 10 5 10 4 10 3 10 2 10 1 10 5 10 4 10 3 10 2 and Crh2p (Rodriguez-Pena et al, 2000) and prokaryotic endo-β-1,3-1,4-glucanases (Tabernero et al, 1994). To assess whether the soluble YlC-rh1S and YlCrh2S proteins have glycosidase activity, we purified the proteins by His affinity chromatography.…”
Section: Glycosidase Activity Of Purified Soluble Ylcrh1s and Ylcrh2smentioning
confidence: 99%
“…The optimum temperature and pH for enzyme activity are 65-70°C and 8-10, respectively. Tabernero et al also reported the cloning and DNA sequencing of bgaA, a gene encoding an endo-(1,3-1,4)-/3-glucanase [94]. /3-Lactamases are important enzymes in antibiotic resistance mechanisms and chemotherapy as they can inactivate penicillins or cephalosporins by hydrolysis.…”
Section: Other Enzymesmentioning
confidence: 99%
“…In addition to the conserved catalytic site of the GH16 family, Crh1 and Crh2 show several structural features, such as a secretory signal peptide at the N-terminus, a family 18 chitin-binding domain [carbohydrate-binding module (CBM)18], which is missing in Crh1, a Ser-Thr-rich region and a GPI attachment signal, which is necessary for their anchoring to the plasma membrane [17]. Bacterial 1-3, 1-4-b-glucanases or lichenases, included in the GH16 family, hydrolyze linear b-glucans containing b-1,3 and b-1,4 linkages with a cleavage specificity for b-1,4 glycosidic bonds [18,19], whereas plant xyloglucan endotransglycosylases catalyze endotype hydrolysis of xyloglucan molecules and the linking of the newly generated reducing end to another xyloglucan molecule [20,21]. The catalytic mechanism for GH16 family was first deduced by 1 H-NMR monitoring for the endo-1,3-1,4-b-D-glucan glucanohydrolase from Bacillus licheniformis [22].…”
Section: Introductionmentioning
confidence: 99%